Strategy of Dynamic Governance in Strengthening the Management of PTKIN Student Boarding Schools in the Era of the Covid-19 Pandemic - Nasrudin, Nasrudin; Ubaidillah, Ubaidillah (Lafadz Jaya Publisher, 2023)
This paper discusses the policy of managing Islamic boarding schools for students of UIN Maliki Malang and IAIN Purwokerto as an answer to the challenges of the times that integrative Islamic human resources can be realized through Islamic boarding school programs for Islamic university students, which also solve the dichotomous problem of science. A dynamic governance perspective was used to see how to manage students' boarding schools and whether they were responsive and creative in the face of challenges that came and went and in this research year, the big challenge was the COVID-19 pandemic. This research uses qualitative research methods using snowball interview techniques, and focus group discussions and involves observation to capture reality to answer this research question. The result of this study is that the Islamic boarding school policy for students at State Islamic universities is a form of integration and interconnection of general science and Islam in the design of human resource development. Islamic boarding schools of IAIN Purwokerto chose to survive amid the spread of covid, manage risks and undergo accelerated vaccination towards livestock communities to be healthy and survive in the long term. The most prominent of the Maliki Malang UIN Islamic boarding school management policy is the online policy.